2018
DOI: 10.3390/ijerph15020345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Health, Social Network and Capital on Craft Efficiency and Productivity: A Case Study of Construction Workers in China

Abstract: The construction industry has been recognized, for many years, as among those having a high likelihood of accidents, injuries and occupational illnesses. Such risks of construction workers can lead to low productivity and social problems. As a result, construction workers’ well-being should be highly addressed to improve construction workers’ efficiency and productivity. Meanwhile, the social support from a social network and capital (SNC) of construction workers has been considered as an effective approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 133 publications
(151 reference statements)
2
34
0
Order By: Relevance
“…Managerial networking significantly facilitates SMEs in the improvement of health and safety management practices such as safety training, worker involvement, safety rules and procedures, and safety promotion and policies. The finding is in line with Yuan et al [66] who demonstrated that external relationship and networking of top managers stimulates their interest of health and safety management practices. We confirmed that managerial networking significantly improves health and safety management practices in the emerging market Pakistan.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Managerial networking significantly facilitates SMEs in the improvement of health and safety management practices such as safety training, worker involvement, safety rules and procedures, and safety promotion and policies. The finding is in line with Yuan et al [66] who demonstrated that external relationship and networking of top managers stimulates their interest of health and safety management practices. We confirmed that managerial networking significantly improves health and safety management practices in the emerging market Pakistan.…”
Section: Discussionsupporting
confidence: 90%
“…In developing economies such as Pakistan, government holds valued resources that may not be accessible unless firms built a network with government and political bodies [65]. Furthermore, the network of top managers with external bodies and organizations is very helpful in improving producing and health practices [66]. Therefore, we posit the following hypotheses: Hypothesis 4 (H4).…”
Section: External Factors and Health And Safety Management Practicesmentioning
confidence: 99%
“…The construction industry has one of the greatest accident rates worldwide [1], and an elevated probability of injuries and occupational illnesses [2]. In Chile, the construction industry has an accident rate of 3.9%, much higher than the national average of 3.1%, considering 38 casualties due to work related accidents in 2018 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The construction sector registers very high labor accident rates in relation to the indices of other activity sectors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and as a consequence, there are high costs associated with work accidents that may depend on the culture, the risk level, the number of operators and the participation of subcontractors on each project [ 8 , 9 , 10 , 11 ]. Even López-Valcarcel [ 12 ] has written that more than half of all workplace injuries and deaths worldwide are attributed to, or are the responsibility of, the construction industry [ 13 ].…”
Section: Introductionmentioning
confidence: 99%